I-Review: Sharing Code. (February 2014) - Kubilius, Jonas
Sharing code is becoming increasingly important in the wake of Open Science. In this review I describe and compare two popular code-sharing utilities, GitHub and Open Science Framework (OSF). GitHub is a mature, industry-standard tool but lacks focus towards researchers. In comparison, OSF offers a one-stop solution for researchers but a lot of functionality is still under development. I conclude by listing alternative lesser-known tools for code and materials sharing.